PSXVII-6 Myths and misconceptions about small ruminant gastrointestinal parasites control. (7th December 2018) - Escobar, E
Abstract: Small ruminant helminthosis (worm burdens) is a problem in agro-climatic zones worldwide. The objective of this poster is to identify 7 examples of myths which are widespread in cyberspace and that potentially jeopardize the parasite load status in the flock or herd. Many sheep and goat producers consider the easily-accessible and free Internet information as a validated knowledge. Most economic losses are due to what is known as "sub-clinical nematodiasis, " which is not immediately observed and not even measured by small ruminant farmers. Additionally, anthelminticresistance (AR) is a global problem threatening the welfare and existence of sheep and goats'. AR represents a challenge in eroding the productivity of small ruminants, thus affecting the survival of small family farms. AR is identified when a previously used anthelmintic ceases to kill an exposed worm population at the therapeutically recommended dosage. Extension educators face the challenge to convey evidence-based practices to their clientele to manage worm burdens, competing…unfortunately, with a huge and ever-growing body of information via the Internet. Examples of the misconceptions and myths are: All livestock have parasites, even humans, …parasites are not a problem for sheep and goats….it is normal…sheep and goats are tough "Natural dewormers" are successfully used as a thoughtful blend and harmony with nature… Increasing or decreasing the recommended dose per animal is irrelevant; if 2 cc are good, then 3 cc are better, or … …use 1 cc …it is cheaper. Treat small ruminants with anthelmintics on a schedule…every month… Use of diatomaceous earth to treat internal parasites in sheep and goats. Soak grains, forage, etc., in a lye solution and give it to the sheep or goats to kill the worms… Extension educators may use this information to enhance their knowledge on integrated parasite management.